Thursday
March 23, 2017

Post a New Question

Posted by on Wednesday, October 27, 2010 at 5:26pm.

hi!
ok, i know that deriv(cscx) = -cscxcotx
and that
deriv(cos) = -sinx
deriv(cotx) = -((cscx)^2)

my question is:
is this (statements below) correct?


antideriv(cscxcotx) = -(cscx)


antideriv(sinx) = -cosx

antideriv((cscx)^2)= -cotx



were those antiderivatives above correct?

  • ap calc bc - , Wednesday, October 27, 2010 at 5:36pm

    yes.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question